Evaluating Hg speciation in an offshore gas export pipeline and the utility of pXRF for screening Hg contamination - Lhiam Paton; Bernt Johannessen; Peter Kappen; Pauline Treble; Jessica Hamilton; Tom Cresswell (Journal of Hazardous Materials, 2026)

Characterising subsea gas pipeline contaminants to inform decommissioning practices, an ecosystem perspective - Tom Cresswell; Henri Wong; Matthew Johansen; Peter Kappen; Jessica Hamilton; Francesca Gissi; Sue Brown; Lhiam Paton; Simon Apte (Journal of Hazardous Materials, 2026)

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Optimizing bromoform content in Gracilaria parvispora: the role of environmental stressors - Steven R. Cunningham; Luke Gardner; Maxime M. Grand; Jessica Metter; Ava Salmi; Evan Simpson; Michael Graham; Scott L. Hamilton; Michael R. Schuppenhauer; Daniel J. Gossard (Journal of Applied Phycology, 2025)

Forecasting hotspots of climatic suitability for grassland restoration under climate change in North America - Santosh Kumar Rana; Jessica Lindstrom; Melissa A. Lehrer; Marissa Ahlering; Jill Hamilton (Biological Conservation, 2025)

Is beudantite a stable host phase of arsenic and lead? New insights from molecular-scale kinetic analyses - A.S.M. Fazle Bari; Girish Choppala; Dane Lamb; Jessica L. Hamilton; CI Sathish; Mohammad Mahmudur Rahman; Ravi Naidu; Robert Aughterson; Edward D. Burton (Journal of Hazardous Materials, 2024)

Comparison between Co(II) and Ni(II) cycling at goethite-water interfaces: Interplay with Fe(II)-catalyzed recrystallization - Zhen Wang; Maximilian Mann; Jessica L. Hamilton; Jeremy L. Wykes; Andrew J. Frierdich (Geochimica et Cosmochimica Acta, 2024)

Multinational evaluation of genetic diversity indicators for the Kunming‐Montreal Global Biodiversity Framework - Alicia Mastretta‐Yanes; Jessica M. da Silva; Catherine E. Grueber; Luis Castillo‐Reina; Viktoria Köppä; Brenna R. Forester; W. Chris Funk; Myriam Heuertz; Fumiko Ishihama; Rebecca Jordan; Joachim Mergeay; Ivan Paz‐Vinas; et al. (Ecology Letters, 2024)
Under the recently adopted Kunming‐Montreal Global Biodiversity Framework, 196 Parties committed to reporting the status of genetic diversity for all species. To facilitate reporting, three genetic diversity indicators were developed, two of which focus on processes contributing to genetic diversity conservation: maintaining genetically distinct populations and ensuring populations are large enough to maintain genetic diversity. The major advantage of these indicators is that they can be estimated with or without DNA‐based data. However, demonstrating their feasibility requires addressing the methodological challenges of using data gathered from diverse sources, across diverse taxonomic groups, and for countries of varying socio‐economic status and biodiversity levels. Here, we assess the genetic indicators for 919 taxa, representing 5271 populations across nine countries, including megadiverse countries and developing economies. Eighty‐three percent of the taxa assessed had data available to calculate at least one indicator. Our results show that although the majority of species maintain most populations, 58% of species have populations too small to maintain genetic diversity. Moreover, genetic indicator values suggest that IUCN Red List status and other initiatives fail to assess genetic status, highlighting the critical importance of genetic indicators.

Population origin and heritable effects mediate road salt toxicity and thermal stress in an amphibian - Lauren M. Conner; Debora Goedert; Sarah W. Fitzpatrick; Amber Fearnley; Emma L. Gallagher; Jessica D. Peterman; Mia E. Forgione; Sophia Kokosinska; Malik Hamilton; Lydia A. Masala; Neil Merola; Hennesy Rico; et al. (Chemosphere, 2024)

Composition and speciation of volcanic volatiles on the Moon - Matthew Varnam; Christopher W. Hamilton; Igor Aleinov; Jessica J. Barnes (Icarus, 2024)

Migration of transition metals and potential for carbon mineralization during acid leaching of processed kimberlite from Venetia diamond mine, South Africa - Baolin Wang; Nina Zeyen; Sasha Wilson; Makoto J. Honda-McNeil; Jessica L. Hamilton; Konstantin Von Gunten; Daniel S. Alessi; Thomas R. Jones; David J. Paterson; Gordon Southam (Applied Geochemistry, 2024)

Reductive sorption of vanadium by iron monosulfide in seawater - Felicia J. Haase; Colton J. Vessey; Ryo Sekine; Nicholas J.C. Doriean; David T. Welsh; Joseph A. Otte; Jessica Hamilton; Donald E. Canfield; Yun Wang; Enzo Lombi; William W. Bennett (Chemical Geology, 2024)

Reductive sorption of vanadium by green rust in seawater - Felicia J. Haase; Colton J. Vessey; Ryo Sekine; David Welsh; Jessica Hamilton; Yun Wang; Jessica White; Donald E. Canfield; Enzo Lombi; William W. Bennett (Geochimica et Cosmochimica Acta, 2023)

Abiotic reduction of nitrate to ammonium by iron (oxy)(hydr)oxides and its stable isotope (δ15N, δ18O) dynamics - Xin Wang; Naomi S. Wells; Wei Xiao; Jessica L. Hamilton; Adele M. Jones; Richard N. Collins (Geochimica et Cosmochimica Acta, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Self-replicating murine ex vivo cultured alveolar macrophages as a model for toxicological studies of particle-induced inflammation - Rebekah L. Kendall; Jessica L. Ray; Raymond F. Hamilton; Andrij Holian (Toxicology and Applied Pharmacology, 2023)

Reduced representation sequencing to understand the evolutionary history of Torrey pine ( Pinus torreyana parry) with implications for rare species conservation - Lionel N. Di Santo; Sean Hoban; Thomas L. Parchman; Jessica W. Wright; Jill A. Hamilton (Molecular Ecology, 2022)
Understanding the contribution of neutral and adaptive evolutionary processes to population differentiation is often necessary for better informed management and conservation of rare species. In this study, we focused on Pinus torreyana Parry (Torrey pine), one of the world's rarest pines, endemic to one island and one mainland population in California. Small population size, low genetic diversity, and susceptibility to abiotic and biotic stresses suggest Torrey pine may benefit from interpopulation genetic rescue to preserve the species' evolutionary potential. We leveraged reduced representation sequencing to tease apart the respective contributions of stochastic and deterministic evolutionary processes to population differentiation. We applied these data to model spatial and temporal demographic changes in effective population sizes and genetic connectivity, to identify loci possibly under selection, and evaluate genetic rescue as a potential conservation strategy. Overall, we observed exceedingly low standing variation within both Torrey pine populations, reflecting consistently low effective population sizes across time, and limited genetic differentiation, suggesting maintenance of gene flow between populations following divergence. However, genome scans identified more than 2000 candidate SNPs potentially under divergent selection. Combined with previous observations indicating population phenotypic differentiation, this indicates natural selection has probably contributed to the evolution of population genetic differences. Thus, while reduced genetic diversity, small effective population size, and genetic connectivity between populations suggest genetic rescue could mitigate the adverse effects of rarity, evidence for adaptive differentiation suggests genetic mixing could disrupt adaptation. Further work evaluating the fitness consequences of inter‐population admixture is necessary to empirically evaluate the trade‐offs associated with genetic rescue in Torrey pine.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Assessing prevalence and correlates of blue-colored flesh in lingcod (Ophiodon elongatus) across their geographic range - Aaron W. E. Galloway; Anne H. Beaudreau; Michael D. Thomas; Bonnie L. Basnett; Laurel S. Lam; Scott L. Hamilton; Kelly S. Andrews; Julie B. Schram; Jessica Watson; Jameal F. Samhouri (Marine Biology, 2021)
Intraspecific variation in external and internal pigmentation is common among fishes and explained by a variety of biological and ecological factors. Blue-colored flesh in fishes is relatively rare but has been documented in some species of the sculpin, greenling, and perch families. Diet, starvation, photoprotection, and camouflage have all been suggested as proximate mechanisms driving blue flesh, but causal factors are poorly understood. We evaluated the relative importance of biological and spatial factors that could explain variation in blue coloration in 2021 lingcod ( Ophiodon elongatus ) captured across their range in the northeastern Pacific, from southeast Alaska to southern California. The probability of having blue flesh was highest for fish that were female, caught in shallower water, and smaller in body size. The incidence of blueness varied by region (4–25% of all fish) but was also confounded by differences in sex ratios of fish caught among regions. We analyzed the multivariate fatty acid composition of a subset of 175 fish from across the sampling range to test for differences in trophic biomarkers in blue lingcod. Lingcod fatty acid composition differed between regions and flesh colors but not between sexes. Blue-fleshed fish had lower concentrations of total fatty acids, 18:1ω-9, 16:1ω-7, 18:1ω-7, and ω-6 fatty acids, suggesting differences in energetics and energy storage in blue fish. While our data indicate potential links between diet and blue flesh in lingcod, important questions remain about the physiological mechanisms governing blueness and its biological consequences.

Estimating cancer treatment intensity from SEER cancer registry data: methods and implications for population-based registry studies of pediatric cancers - Jessica L. Tobin; Stefanie M. Thomas; David R. Freyer; Ann S. Hamilton; Joel E. Milam (Cancer Causes & Control, 2020)

Iodine status in western Kenya: a community-based cross-sectional survey of urinary and drinking water iodine concentrations - Michael J. Watts; Daniel R. S. Middleton; Andrew Marriott; Olivier S. Humphrey; Elliott Hamilton; Valerie McCormack; Diana Menya; Jessica Farebrother; Odipo Osano (Environmental Geochemistry and Health, 2020)

Carbon and nitrogen recycling during cyanoHABs in dreissenid-invaded and non-invaded US midwestern lakes and reservoirs - Trinity L. Hamilton; Jessica R. Corman; Jeff R. Havig (Hydrobiologia, 2020)
Lakes and reservoirs play key roles in global carbon cycling, especially as a carbon sink. Enrichment of nutrients in lakes and reservoirs (eutrophication) and rising global temperatures favors the proliferation of bloom-forming cyanobacteria. Harmful blooms of cyanobacteria (cyanoHABs) alter carbon and nutrient cycling in freshwater ecosystems. Some evidence suggests the introduction or establishment of invasive mussel species (i.e., Dreissena spp.) also favor cyanoHAB formation through selective filter feeding, a process through which they may also impact biogeochemical processes including carbon cycling and sequestration. However, few studies have considered the combined effects of invasive mussels and cyanoHABs on carbon and nitrogen cycling in freshwater ecosystems. Here, we examined microbial community composition and biogeochemical attributes (including carbon and nitrogen stable isotopes) in eutrophic lakes, reservoirs, and rivers in western Ohio, eastern Indiana, and northern Kentucky during the cyanobacterial bloom period of the summer of 2015. Our samples include both sites impacted by invasive mussels and those where invasive mussels have not yet been observed. Based on 16S and 18S rRNA gene sequence analysis, we found that cyanobacterial and algal communities varied across sites and were most closely related to habitat (sediment or water column sample) and site, regardless of the presence of invasive mussels or other environmental factors. However, we did find evidence that invasive mussels may influence both carbon and nitrogen cycling. While the results are based on a single time point sampling, they highlight the interactions of multiple environmental stressors in aquatic ecosystems and the critical need for more temporally intensive studies of carbon and nutrient cycling in bloom- and mussel-impacted waters.

Potential for offsetting diamond mine carbon emissions through mineral carbonation of processed kimberlite: an assessment of De Beers mine sites in South Africa and Canada - Evelyn M. Mervine; Sasha Wilson; Ian M. Power; Gregory M. Dipple; Connor C. Turvey; Jessica L. Hamilton; Sterling Vanderzee; Mati Raudsepp; Colette Southam; Juerg M. Matter; Peter B. Kelemen; Johann Stiefenhofer; et al. (Mineralogy and Petrology, 2018)

Pathogenetics of alveolar capillary dysplasia with misalignment of pulmonary veins - Przemyslaw Szafranski; Tomasz Gambin; Avinash V. Dharmadhikari; Kadir Caner Akdemir; Shalini N. Jhangiani; Jennifer Schuette; Nihal Godiwala; Svetlana A. Yatsenko; Jessica Sebastian; Suneeta Madan-Khetarpal; Urvashi Surti; Rosanna G. Abellar; et al. (Human Genetics, 2016)

siRNA-Mediated Knockdown of P450 Oxidoreductase in Rats: A Tool to Reduce Metabolism by CYPs and Increase Exposure of High Clearance Compounds - Rob S. Burke; Inthirai Somasuntharam; Paul Rearden; Duncan Brown; Sujal V. Deshmukh; Martha A. DiPietro; Jillian DiMuzio; Roy Eisenhandler; Scott E. Fauty; Christopher Gibson; Marian E. Gindy; Kelly A. Hamilton; et al. (Pharmaceutical Research, 2014)

Land Management Restrictions and Options for Change in Perpetual Conservation Easements - Adena Rissman; Menka Bihari; Christopher Hamilton; Christina Locke; David Lowenstein; Melissa Motew; Jessica Price; Robert Smail (Environmental Management, 2013)